Kajian Potensi Pembangkit Listrik Tenaga Mikrohidro Di Sungai Wae Bobot Kecamatan Werinama Kabupaten Seram Bagian Timur - Kelian, Mohamad Achmad Sofyan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2017)
This research study exploiting of potency charge river alternatively resource of energi for the power station ofhydro mini energy ( PLTMH). Case study the evaluated is Wai Bobot River which located in CountrysideFragon Enchain, District Of Field Jar Pate;Upstream, Sub-Province of Werinama Kab. Seram Bagian Timur.Power Station Of Hydro Mini Energy ( PLTMH) expected can be woke up by Local Government Of Sub-Province of Werinama Kab.Seram Bagian Timur to obtain;get energy capacities attached equal to 27 kW to 42house and 0,514 kW to each;every house by exploiting Wai Bobot River. Dimension Building barricade PLTMHspecified from pursuant to River Wai Bobot floods debit equal to Q= 55 m3 / det. Debit plan equal to 0,80 m3 /det obtained from result of direct measurement in field by considering various aspect for example : yieldedenergy, scheme of PLTMH, high fall, turbine operational and also defrayal of work of and civil of elektromekanikallowest.